Lepidus the Archiereus of Pontus: Guardian of Amastris against the Cult of Glykon? - Ching-Yuan Wu (The Ninth International Conference of the Taiwan Association of Classical, Medieval and Renaissance Studies., 2015)
Lucian’s short pamphlet Ἀλέξανδρος ἢ Ψευδόμαντις (Alexander, or The False Prophet) gives an account on how a conjurer by the name of Alexander concocted a syncretistic snake oracle to victimize Paphlagonians. Alexander met resistence, however. Lucian claims that Amastris in particular was Alexander’s most despised city in Pontus, because “the followers of Lepidus and others like them were numerous in the city; and he would never deliver an oracle to an Amastrian” (Luc. Alex. 25). While the snake oracle is widely attested on coins, statues and iconography, there is no corroborating evidence on Alexander of Abonuteichos and Lepidus of Amastris beyond Lucian’s text. Yet, scholars used two inscriptions mentioning a Tiberius Claudius Lepidus (CIG 4149 & 4150, now lost) to establish Lepidus as a historical figure (Robert 1980: 146; Marek 1993: 98; Gordon 1996: 114; Victor 1997: 151). The rationale behind this identification, however, seems to have only been based on the identical cognomen and the hypothesis that the inscribed Lepidus, being an archpriest of Pontus (ἀρχιερεύς τοὺ Πόντου), controlled both the sacred and the profane domains of Amastris. After a literature review concerning the historicity of Lucian’s Alexander and Lucian’s Lepidus, this paper presents a close reading of the Lepidus inscriptions from Amastris previous studies. Since previous studies seldom considered the definitions and functions of the different types of archpriesthood found in Amastris, this paper studies Amastrian inscriptions and associated literature to establish context. A reassessment of the hypothesis that Lepidus controlled the religious domain of Amastris during the Antonine period will conclude the paper.